The “Mr. and Mrs. Ghat crab”, Ghatiana dvirupa sp. nov. (Decapoda: Brachyura: Gecarcinucidae) from the Central Western Ghats of India - Pati, Sameer Kumar; Bajantri, Parashuram Prabhu; Hegde, Gopalkrishna Dattatraya (Zootaxa, 2024)
A new species of gecarcinucid freshwater crab, Ghatiana dvirupa sp. nov., is described herein from the Kali Tiger Reserve of the Uttara Kannada district, Karnataka state, India. The Kali Tiger Reserve is a protected area, which is situated in the Central Western Ghats. The new species superficially most resembles Ghatiana sanguinolenta Pati, Thackeray & Pawar, 2023, from Karnataka but can easily be distinguished mainly by its ultimate article of the male first gonopod, which is distally gently curved inwards against the gently outwardly curved distal portion of the ultimate article in the latter species. Ghatiana dvirupa sp. nov. is also compared with the remaining species of the genus from Karnataka and some morphologically related species from Maharashtra. The difference in colour in life has been noticed between males and females of G. dvirupa sp. nov.; as such the common name of the new species is proposed as “Mr. and Mrs. Ghat Crab”. Ghatiana Pati & Sharma, 2014, is now known for 13 species, all from the Western Ghats of India. Karnataka currently possesses six species of Ghatiana, and many new species are yet to be described.